2002
DOI: 10.1017/s1355838202011184
|View full text |Cite
|
Sign up to set email alerts
|

Human ribonuclease P: Subunits, function, and intranuclear localization

Abstract: Catalytic complexes of nuclear ribonuclease P (RNase P) ribonucleoproteins are composed of several protein subunits that appear to have specific roles in enzyme function in tRNA processing. This review describes recent progress made in the characterization of human RNase P, its relationship with the ribosomal RNA processing ribonucleoprotein RNase MRP, and the unexpected evolutionary conservation of its subunits. A new model for the biosynthesis of human RNase P is presented, in which this process is dynamic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
68
0
2

Year Published

2003
2003
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 82 publications
2
68
0
2
Order By: Relevance
“…Furthermore, RNase P-catalyzed cleavage has also been suggested to play a role in mRNA degradation and regulation of gene expression in vivo . In most organisms, RNase P consists of a catalytically active RNA subunit (PRNA) associated with one or more protein cofactors (P proteins) essential for in vivo activity (Hall and Brown 2002;Jarrous 2002;Hsieh et al 2004;Evans et al 2006;Walker and Engelke 2006;Gopalan 2007;Jarrous and Reiner 2007). Given the essential and universal role of this enzyme, it is fundamentally important to understand the mechanisms of molecular recognition and catalysis used by RNase P.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, RNase P-catalyzed cleavage has also been suggested to play a role in mRNA degradation and regulation of gene expression in vivo . In most organisms, RNase P consists of a catalytically active RNA subunit (PRNA) associated with one or more protein cofactors (P proteins) essential for in vivo activity (Hall and Brown 2002;Jarrous 2002;Hsieh et al 2004;Evans et al 2006;Walker and Engelke 2006;Gopalan 2007;Jarrous and Reiner 2007). Given the essential and universal role of this enzyme, it is fundamentally important to understand the mechanisms of molecular recognition and catalysis used by RNase P.…”
Section: Introductionmentioning
confidence: 99%
“…Several human proteins (corresponding to homologs of Pop1, Pop3, Pop4, and Pop8 in yeast) were shown to accumulate in the nucleolus, suggesting that they might be involved in localization of RNase MRP and P (Jarrous et al 1999;van Eenennaam et al 2001). Several overexpressed human RNase P proteins were shown to selectively bind to precursor tRNA, suggesting that they might be involved in interaction with the substrate in the holoenzyme (Jarrous 2002). Filter binding assays (Aspinall et al 2007) suggested that individually expressed yeast proteins Pop4, Pop6, Rmp1, and Snm1 might interact with the RNase MRP pre-rRNA substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Eukaryotic RNase P has a very similar RNA moiety, but the protein complement is far more complex than that of the bacterial enzyme. Nine-and 10-protein subunits have been identified in the nuclear RNase P from yeast and humans, respectively (Chamberlain et al 1998;Jarrous 2002). The eukaryotic RNase P RNA appears to have lost the ability to cleave pre-tRNAs in the absence of the protein subunits.…”
Section: Introductionmentioning
confidence: 99%